(untitled) (Journal of Pathology of Nepal, 2024)
Background: Ultra Papanicolaou stain was introduced as a hybrid of Romanowsky and Papanicolaou stains. It enhances the quality and reduces the time. Materials and Methods: Five hundred and ninety-five fine needle aspiration and body fluid samples were collected. The fine needle aspiration procedure was performed by standard method; smears were fixed in 95% propanol and stained with conventional and ultra Papanicolaou stains. Four parameters were considered and scored (background, cell morphology, nuclear staining, and overall staining pattern). Results: The quality of ultra Papanicolaou stain smears was better than conventional pap stain, and this difference was statistically significant. Conclusions: UltraPap stain, compared to conventional Pap stain, provides an excellent alternative in cytological staining for the evaluation of various organs and fluids for benign and malignant pathology.